Sic Semper Tyrannis the Philosophy of Law and the Right to Fight Tyranny - Kuznetsov, Michael Yurievich (Journal of Current Social and Political Issues, 2025)
This essay explores the philosophical underpinnings of the right to kill a tyrant within the framework of legal philosophy, examining its ontological, epistemological, and axiological dimensions. The discussion delineates major schools of legal philosophy—natural law (Grotius, Cicero), positive law (Aquinas, Bentham, Austin, Hart), utilitarian law (Hume, Bentham, Mill, Sidgwick), Marxist law (Marx, Engels), historical school (Montesquieu, Hugo, Savigny), sociological jurisprudence (Jhering, Gerber), and realist jurisprudence (Holmes, Llewellyn, Morgenthau)—while selectively employing all except positivist and realist approaches. Natural law, decoupled from divine origins by Grotius, prioritizes inherent human rights, whereas utilitarianism evaluates actions by their promotion of happiness, critiqued by Constant for subordinating principle to outcome. Tyrannicide evolves from class-based resistance in feudal societies to a democratic imperative in modernity, rooted in natural rights. The author laments the absence of "tyrant" definitions in contemporary constitutions (e.g., Ukrainian, U.S., French and etc.), viewing it as enabling elite manipulation. Advocating legislative reforms to permit tyrannicide, the paper warns against nihilism while affirming life's value, favoring imprisonment over execution in liberal states. Drawing on Boesche and Kelsen, it portrays justice as relativistic yet essential for democracy, urging ongoing discourse to safeguard freedoms.